# Logarithm and Exponential Questions with Answers and Solutions - Grade 12

The concepts of logarithm and exponential are used throughout mathematics. Questions on Logarithm and exponential with solutions, at the bottom of the page, are presented with detailed explanations.

1. Solve the equation (1/2)2x + 1 = 1
2. Solve x ym = y x3 for m.
3. Given: log8(5) = b. Express log4(10) in terms of b.
4. Simplify without calculator: log6(216) + [ log(42) - log(6) ] / log(49)
5. Simplify without calculator: ((3-1 - 9-1) / 6)1/3
6. Express (logxa)(logab) as a single logarithm.
7. Find a so that the graph of y = logax passes through the point (e , 2).
8. Find constant A such that log3 x = A log5x , for all x > 0.
9. Solve for x the equation log [ log (2 + log2(x + 1)) ] = 0
10. Solve for x the equation 2 x b4 logbx = 486
11. Solve for x the equation ln (x - 1) + ln (2x - 1) = 2 ln (x + 1)
12. Find the x intercept of the graph of y = 2 log( √(x - 1) - 2)
13. Solve for x the equation 9x - 3x - 8 = 0
14. Solve for x the equation 4x - 2 = 3x + 4
15. If logx(1 / 8) = -3 / 4, than what is x?

Solutions to the Above Problems

1. Rewrite equation as (1/2)2x + 1 = (1/2)0
Leads to 2x + 1 = 0
Solve for x: x = -1/2

2. Divide all terms by x y and rewrite equation as: ym - 1 = x2
Take ln of both sides (m - 1) ln y = 2 ln x
Solve for m: m = 1 + 2 ln(x) / ln(y)

3. Use log rule of product: log4(10) = log4(2) + log4(5)
log4(2) = log4(41/2) = 1/2
Use change of base formula to write: log4(5) = log8(5) / log8(4) = b / (2/3) , since log8(4) = 2/3
log4(10) = log4(2) + log4(5) = (1 + 3b) / 2

4. log6(216) + [ log(42) - log(6) ] / log(49)
= log6(63) + log(42/6) / log(72)
= 3 + log(7) /2 log(7) = 3 + 1/2 = 7/2

5. ((3-1 - 9-1) / 6)1/3
= ((1/3 - 1/9) / 6)1/3
= ((6 / 27) / 6)1/3 = 1/3

6. Use change of base formula: (logxa)(logab)
= logxa (logxb / logxa) = logxb

7. 2 = logae
a2 = e
ln(a2) = ln e
2 ln a = 1
a = e1/2

8. Use change of base formula using ln to rewrite the given equation as follows
ln (x) / ln(3) = A ln(x) / ln(5)
A = ln(5) / ln(3)

9. Rewrite given equation as: log [ log (2 + log2(x + 1)) ] = log (1) , since log(1) = 0.
log (2 + log2(x + 1)) = 1
2 + log2(x + 1) = 10
log2(x + 1) = 8
x + 1 = 28
x = 28 - 1

10. Note that b4 logbx = x4
The given equation may be written as: 2x x4 = 486
2 x5 = 486
x = 2431/5 = 3

11. Group terms and use power rule: ln (x - 1)(2x - 1) = ln (x + 1)2
ln function is a one to one function, hence: (x - 1)(2x - 1) = (x + 1)2
Solve the above quadratic function: x = 0 and x = 5
Only x = 5 is a valid solution to the equation given above since x = 0 is not in the domain of the expressions making the equations.

12. Solve: 0 = 2 log( √(x - 1) - 2)
Divide both sides by 2: log( √(x - 1) - 2) = 0
Use the fact that log(1)= 0: √(x - 1) - 2 = 1
Rewrite as: √(x - 1) = 3
Raise both sides to the power 2: (x - 1) = 32
x - 1 = 9
x = 10

13. Given: 9x - 3x - 8 = 0
Note that: 9x = (3x)2
Equation may be written as: (3x)2 - 3x - 8 = 0
Let y = 3x and rewrite equation with y: y2 - y - 8 = 0
Solve for y: y = ( 1 + √(33) ) / 2 and ( 1 - √(33) ) / 2
Since y = 3x, the only acceptable solution is y = ( 1 + √(33) ) / 2
3x = ( 1 + √(33) ) / 2
Use ln on both sides: ln 3x = ln [ ( 1 + √(33) ) / 2]
Simplify and solve: x = ln [ ( 1 + √(33) ) / 2] / ln 3

14. Given: 4x - 2 = 3x + 4
Take ln of both sides: ln ( 4x - 2 ) = ln ( 3x + 4 )
Simplify: (x - 2) ln 4 = (x + 4) ln 3
Expand: x ln 4 - 2 ln 4 = x ln 3 + 4 ln 3
Group like terms: x ln 4 - x ln 3 = 4 ln 3 + 2 ln 4
Solve for x: x = ( 4 ln 3 + 2 ln 4 ) / (ln 4 - ln 3) = ln (34 * 42) / ln (4/3) = ln (34 * 24) / ln (4/3)
= 4 ln(6) / ln(4/3)

15. Rewrite the given equation using exponential form: x- 3 / 4 = 1 / 8
Raise both sides of the above equation to the power -4 / 3: (x- 3 / 4)- 4 / 3 = (1 / 8)- 4 / 3
simplify: x = 84 / 3 = 24 = 16

More on